Rapid early‐Holocene deglaciation in the Ross Sea, Antarctica. Issue 15 (12th August 2017) - Spector, Perry; Stone, John; Cowdery, Seth G.; Hall, Brenda; Conway, Howard; Bromley, Gordon
Abstract: Deglaciation of the Ross Sea following the last ice age provides an important opportunity to examine the stability of marine ice sheets and their susceptibility to changing environmental conditions. Insufficient chronology for Ross Sea deglaciation has helped sustain (i) the theory that this region contributed significantly to Meltwater Pulse 1A (MWP‐1A) and (ii) the idea that Ross Sea grounding‐line retreat occurred in a "swinging gate" pattern hinged north of Roosevelt Island. We present deglaciation records from southern Transantarctic Mountain glaciers, which delivered ice to the central Ross Sea. Abrupt thinning of these glaciers 9–8 kyr B.P. coincided with deglaciation of the Scott Coast, ∼800 km to the north, and ended with the Ross Sea grounding line near Shackleton Glacier. This deglaciation removed grounded ice from most of the central and western Ross Sea in less than 2 kyr. The Ross Sea Sector neither contributed nor responded significantly to MWP‐1A. Key Points: Much of the central and western Ross Sea deglaciated abruptly ∼9‐8 kyr B.P. The Ross Sea Sector did not significantly contribute or respond to MWP‐1A Rapid deglaciation was likely influenced by retreat into marine basins and/or enhanced marine melting